An Exploratory Qualitative Study on Indonesian Mothers' Needs and Concerns about Having a Thalassemic Child and Its Treatment - Mediani, Henny Suzana; Nurhidayah, Ikeu; Mardhiyah, Ai; Panigoro, Ramdan (Highlights on Medicine and Medical Science Vol. 18, 2021)
Thalassemia is a major genetic blood disorder that considered as a public health problem in Indonesia. Yet, little is known about affected individuals thalassemic children and parents overall experiences with and perceptions of thalassemia mayor in Indonesia. This study aimed to explore the concerns, beliefs, feelings and needs of mothers' who have a thalassemic child. A total of (N=24) mothers' were chosen as participants. Focus Group Discussion (FGD) was carried out to better elucidate the mothers' perceptions of their needs and concerns. A semi-structure focus group moderator’s guide corresponding to the research questions was developed. To gain in-depth understanding, questions were divided in four major domains which were (i) Perceptions about child disease, (ii) Knowledge about thalassemia and its treatment, (iii) Thalassemia impact on child and family, and (iv) Needs and future concerns. Transcripts were thematically coded according to the research themes that emerged from the data, and the themes were further sorted into subthemes. The finding of this study indicates significant impact of thalassemic children on their families in terms of emotional well-being, financial burden and social impact. Mother’s education level was very low about Thalassemia. Mother also expressed their needs for more information about thalassemia and its treatment, social, professional support, and financial support. Results of this study provided a portrait of the reality that thalassemia has a significant impact on children and their families. A holistic approach should be carried out while caring with thalassemic children and their families. Nurses and health care professionals should explore the feelings, concerns and needs of mothers' who have thalassemic children and eventually provide appropriate care plans that alleviate their suffering.